Decontamination protocols for bovine fecal and environmental samples for culture of Mycobacterium avium subsp. paratuberculosis growth on solid media - Correa-Valencia, Nathalia M.; Hernández-Agudelo, José Miguel; Fernández-Silva, Jorge A. (Austral Journal of Veterinary Sciences, 2024)
Bacteriological culture of Mycobacterium avium subsp. paratuberculosis (MAP) is considered the gold standard to confirm its presence in several matrices for Johne’s disease diagnosis. Whether it is a liquid or solid culture, a problem with MAP culture is that non-interpretable results arise because of overgrowth by other microorganisms, making MAP growth and identification more difficult or impossible. We systematically reviewed published decontamination protocols and their effects on MAP culture from bovine fecal and environmental samples on solid media. Based on our findings, we suggest a step-by-step decontamination protocol. The OVID®/MEDLINE, PubMed®, SciELO Citation Index®, and Redalyc® platforms as well as the International Colloquium on Paratuberculosis (ICP) proceedings and the reference lists were reviewed to identify relevant studies. The inclusion criteria considered articles published in English, Portuguese, French, German, Spanish, and peer-reviewed journals. The exclusion criteria included unrelated topics, species other than bovines, other than environmental/faecal samples, other than diagnostic techniques of interest, and non-original articles. Definitive studies were obtained through the authors’ consensus regarding their eligibility and quality. In total, 1,004 publications matched the search terms, and 27 articles met the inclusion criteria, of which 45 derived and report- ed 15 different decontamination protocols. The centrifugation-one-step hexadecylpyridinium chloride protocol, which used over 22,154 fecal samples in three studies, was found to be the most suitable, reporting an average MAP isolation rate of 3.99% (886/22,154) and an average contamination rate of 0.17% (38/22,154). This systematic review highlights the need for further refinement of decontamination protocols to minimize the loss of viable MAP during processing of bovine fecal and environmental samples.